Pengaruh Capital Adequacy Ratio (Car) Dan Non Performing Loan (Npl) Terhadap Return On Asset (Roa) Pada Pt Bank Pan Indonesia Tbk (Bank Panin) Periode 2014 – 2023 - Ayu Nur Azkavianti; Esti Suntari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research seeks to examine the influence of the Capital Adequacy Ratio (CAR) and Non-Performing Loan (NPL) on Return on Assets (ROA) at PT Bank Pan Indonesia Tbk over the 2014–2023 period. The study employs secondary data derived from the company’s audited annual financial reports, applying a quantitative approach with a descriptive design. Data analysis was conducted through multiple linear regression, supported by the t-test, F-test, and coefficient of determination (R²), using SPSS version 27 as the analytical tool. The findings reveal that, individually, CAR does not exert a significant impact on ROA, as reflected by a significance value of 0.831 > 0.05, and likewise, NPL shows no significant effect on ROA with a significance level of 0.908 > 0.05. Furthermore, the simultaneous test (F-test) confirms that both CAR and NPL jointly do not significantly influence ROA, indicated by a significance value of 0.972 > 0.05. The coefficient of determination (R²) of 0.008 suggests that CAR and NPL together explain only 0.8% of the variation in ROA, leaving 99.2% to be attributed to other factors not included in the model..